A review on intrapreneurship: Individual level with an HRD focus - Pelica, R. O.; Palma, P. J. da.; Velez, M. J. (Human Resource Development Review)
This systematic review on intrapreneurship - individual level, HRD focus - addresses three research questions: What is the definition of intrapreneurship? What are its antecedents and outcomes? And how can it be integrated into HRD practices? Following the PRISMA protocol, twenty-six articles were included (peer review, English written, Q1 or Q2). Using the analysis matrix method, intrapreneurship was defined as an employee-initiated behavior comprising six core dimensions: communication and information, innovativeness, networking and influence, new ventures and opportunities, personal initiative, and risk-taking. Antecedents emerged from personal capabilities, perceptions, personality, self-attitudes and relational contexts. Outcomes included increased knowledge, performance, and participation in innovative projects. Theoretically, positions intrapreneurship as a developmental mechanism central to HRD, offering a novel and original conceptual framework supported by McLagan’s (1989) seven HRD dimensions. For practice, provides HRD professionals with a strategic tool to intentionally integrate intrapreneurial behavior into their learning and development practices.